Answer:
8/25
Explanation:
The given expression x^-2 y^3, where x = -5 and y = 2
Here we have negative exponent, we have to make it positive using exponent rule.
a^-1 = 1/a
Using this rule, we can rewrite the given expression as
=
![(1)/(x^2) * y^3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j0gh947oy3u44nn21sryrr7zfwj497jnlx.png)
Now plug in x = -5 and y = 2, in the above expression, we get
= 1/(-5)^2 *(2)^3
= 1/25 *8
= 8/25
That's the answer.
Hope you will understand the concept.
Thank you.